EUROPEAN CONGRESS OF RHEUMATOLOGY (MADRID, 12–15 JUNE 2013): PROBLEMS ON RHEUMATOID ARTHRITIS - Anastasia Sergeevna Avdeeva; L N Denisov; E L Nasonov (Научно-практическая ревматология, 2013)
An annual European Congress of Rheumatology took place from 12–15 June 2013 in Madrid. The Congress program was extremely diverse; it included discussion of new evidence on the diagnosis and treatment of the most commonrheumatic diseases, their etiology and pathogenesis, personified therapy and more. The optimization of pharmacotherapy for rheumatoid arthritis (RA) and the choice of therapy strategy in different groups of patents occupied acentral place at the Congress. New guidelines for the management of patients with RA were given. A number of reports concerned the efficiency and safety of using tocilizumab in RA, the possibility of discontinuing therapy with genetically engineered biological agents (GEBAs) when achieving a remission, and the maintenance of drug-free remission in RA. The Congress discussed the new results of the AMPLE trial, one of the first direct comparative studies of the efficacy of two GEBAs (subcutaneous formulations of abatacept and adalimumab). A large number of reports dealt with the use of tumor necrosis factor-α inhibitors, the evaluation of their immunogenicity, the analysis of reasons for therapy discontinuation, as well as adverse reactions occurring during treatment. Some aspects of therapy with conventional disease-modifying anti-rheumatic drugs were discussed. Thus, a lot of new data that can optimize therapy for a common rheumatic disease, such as RA, were presented at the Congress.